Screening of Fusarium graminearum isolates for enzymes extracellular and deoxynivalenol production - Ortega, Leonel Maximilano (2013)
Fusarium graminearum, the main etiological agent of Fusarium Head Bligh, has high intraspecific genetic diversity, which is related to the variability in the aggressiveness among isolates against wheat. The aggressiveness involves different mechanisms as the production and liberation of extracellular enzymes and mycotoxins. In the present report, several F. graminearum isolates obtained from wheat spikes from Pampas region, Argentina, were screened for polygalacturonase (pectinase), proteolytic and lipase extracellular enzymatic activities production, as well as by the capacity to produce deoxynivalenol. The enzymatic production in terms of magnitude was varied among isolates, which could be related to a differential capacity to infect wheat. Both polygalacturonase as proteolytic activities had a maximum activity in the first days of incubation. Instead, the lipase activity reached its maximum activity advanced incubation time. Deoxynivalenol production was delayed over time with respect to the first enzymatic activities, which would infer its relation with the progress of the disease in the host, more than with the early stages of infection. The characterization carried out in this research, would allow us to apply a selection criterion among isolates for further research.